Design of a Handicraft Product Marketplace using a Web-Based Business to Consumer (B2C) Method - M.Fajri Hermawan (Journal of Computer Scine and Information Technology, 2022)
West Sumatra is famous for its embroidery. Usually embroidery is found on mukena, hijab, brackets, koko clothes, and others. The issue of marketing and brand promotion is still one of the biggest obstacles for embroidery businesses in increasing their business scale. Embroidery business actors often experience problems in selling their products. This cannot be separated from the tendency of these business actors to focus more on the production process without being balanced by marketing and promotion. Some embroiders, when the goods are available, they are confused about what to do to sell it quickly. As a result, the marketing and promotion steps taken tend to be conventional, namely word of mouth or simply displaying their products in stores. To overcome these problems, the authors conducted research to design a marketplace application to help business people to easily promote their products. In conducting this research the author uses the SDLC method. While the development of software in the design of this decision support system the author uses the PHP programming language. The results of this study are a marketplace application that can make it easier for customers to access products without having to come to the place, make purchases, transfer payments or online anywhere, so as to increase customer buying interest